Analysis of Alpha and Lithium-7 Particle Energy Deposition in BNCT using Geant4 Simulation - Charef, K.; Ahlaf, F. Z.; Khoulaki, Y.; Benchekroun, D.; Harrass, H.; Fathi, I.; Makhkhas, Y. (National Research and Innovation Agency, 2025)
This study investigates the microdosimetric characteristic of Boron Neutron Capture Therapy (BNCT) using high-fidelity Monte Carlo simulations to quantify the energy deposition distributions of alpha and lithium-7 particles within cellular structures. The Geant4 toolkit is utilized to model various physics lists and water representations, aiming to optimize the accuracy of BNCT simulations. Dosimetric and microdosimetric studies using these Monte Carlo techniques are conducted to examine the behavior of the produced alpha and lithium-7 particles and their energy deposition in different cellular compartments. Our findings contribute to the understanding of BNCT’s effects at the cellular level, which is crucial for advancing treatment planning and minimizing side effects.